The Independent Sugarcane Farmer’s Satisfaction Towards Partnership of PT. Perkebunan Nusantara PG Takalar - St. Rahayu Arini Lestari; Didi Rukmana; Musran Munizu (International Journal of Science, Technology & Management, 2021)
This study aims to determine the level of satisfaction of farmers towards to the performance of the partnership. The research was conducted at PG Takalar from April to September 2020. Respondents were 75 farmers. The analytical tools used in this research are IPA (Important Performance Analysis) and CSI (Customer Satisfaction Index). The results showed that the implementation of the partnership activities was in accordance with the partnership cooperation contract between the company and the partner farmers. The farmersare very satisfied with the implementation of the partnership with PG Takalar. The attributes of the partnership that greatly contribute to the satisfaction of the farmers are a clear acceptance of the partnership, technical advice, easy access forfund, compliance of payment results, factory locations easily accessible to farmers and communication relationships that established between farmers and sugar factories.